THE ROLE OF SCIENTIFIC CALCULATORS IN IMPROVING STATISTICS LEARNING - Adila Sosianika; Euis Sartika; Fatya Alty Amalia (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
In its development, Business Statistics has used several types of technology to facilitate the learning process for students, such as statistical software, spreadsheets, calculators, multimedia materials, and data repositories. The calculator includes computer technology with a simple version but allows students to experience an active learning process. Thus, the calculator media was chosen as the main learning media in business statistics courses, including in evaluating student abilities. Therefore, this study aims to determine the effectiveness of using calculators in Business Statistics courses. The research was conducted using a mix method, namely qualitative (questionnaire) and quantitative (experimental). The results showed that there was an increase in the average value of Simple Linear Regression for groups of students who used statistical applications on calculators compared to groups who did not use calculators. Based on the results of the questionnaire and suggestions, it was found that 87.7% of students considered it easy to understand the Business Statistics application questions, when using the statistical application on a calculator. Suggestions made by students were the availability of guidelines for using statistical calculator applications for practice, and the availability of calculators in the research laboratory that students could use for practice